Increased plasma cardiac troponin I concentration in lambs with myocarditis - Karapinar, Tolga; Eroksuz, Yesari; Beytut, Enver; Sozdutmaz, Ibrahim; Eroksuz, Hatice; Dabak, Murat (Wiley-Blackwell, 2012)
Background Cardiac troponin I (cTnI) is a blood biomarker of myocardial injury. A human cTnI assay may be useful for measuring cTnI concentrations in lambs with naturally occurring myocarditis. Objective The aims of this study were to evaluate the utility of a commercially available human chemiluminescent microparticle cTnI immunoassay for measuring plasma cTnI concentrations in lambs with naturally occurring myocarditis from infection with foot and mouth disease virus (FMDV), and to determine cTnI expression in cardiac muscle of affected lambs. Methods Ten lambs with myocarditis and 10 clinically healthy lambs (control group) were included. Clinical signs, gross and histologic necropsy findings, and immunoreactivity for cTnI in cardiac tissue were evaluated. Plasma cTnI concentration was determined using the commercial human immunoassay system. Results All lambs with myocarditis died within 1 similar to day of clinical signs. Infection with FMDV was confirmed by PCR analysis. Gross cardiac lesions were evident and histologic examination revealed myocarditis. Immunoreactivity for cTnI was absent in cardiac myocytes that were degenerative or necrotic, but was strong in cardiac myocytes from unaffected areas of the myocardium and in all cardiac myocytes of healthy lambs. The geometric mean plasma concentrations of cTnI for lambs in the myocarditis and control groups were 146.78 similar to mu g/L (95% confidence interval [CI], 61.90348.06) and 0.013 similar to mu g/L (95% CI, 0.0100.017), respectively (t-value 19.27; P similar to
Keywords: Cardiac necrosis; CMIA; cTnI; heart failure; myocyte; ovine